2-6(-2x+2)=2+5(x-1)

Simple and best practice solution for 2-6(-2x+2)=2+5(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-6(-2x+2)=2+5(x-1) equation:


2-6(-2x+2)=2+5(x-1)

We simplify the equation to the form, which is simple to understand
2-6(-2x+2)=2+5(x-1)

Reorder the terms in parentheses
2+(+12x-12)=2+5*(x-1)

Remove unnecessary parentheses
+2+12x-12=+2+5+*(+x-1+)

Reorder the terms in parentheses
2+12x-12=2+(+5x-5)

Remove unnecessary parentheses
+2+12x-12=+2+5x-5

We move all terms containing x to the left and all other terms to the right.
+12x-5x=+2-5-2+12

We simplify left and right side of the equation.
+7x=+7

We divide both sides of the equation by 7 to get x.
x=1

See similar equations:

| 24x+24-10x=6x-40 | | 43958jdlk=5 | | 0.4x+0.7=-0.9 | | .8w-.6w+.3w=2 | | -17a+4(a-7)=-3(3a-1)+1 | | 15ab+13a-15ab= | | 2m-5m=6 | | 45x+5=50graph | | 3(2x-3)+9=6x | | x+7=-3(5-x) | | 1y=-4 | | (-3)-2.2-9-(-12)= | | 8x-5=2(4x-3) | | 2.2x=-22 | | 3x+12=-3x+20 | | 2(3x+1)+4=2-x | | 18x+2(x+7)=-6 | | 37+12+=85 | | 7x+9=4x+3 | | 0.3x+1.1=3.5 | | 2*(3-x)+7=4x-5*(2+x) | | 0.3+1.1=3.5 | | 2(3-x)+7=4x-5(2+x) | | 5x=3x+20 | | 32-3x=2x-28 | | (22b-9)-7(3b+4)=-4 | | 3x-4(x-2)(X^2+6x^2-1)-7= | | 4x+2-3x=18 | | 5a(a+3)=2a(2a-5) | | 2(3+2w)+1=-5 | | x(x-4)+56=x*x | | 8x+2=3x-2 |

Equations solver categories